The ratio of QRS/RV6-V1: a new electrocardiographic predictor of short- and long-term adverse clinical outcomes in patients with acute myocardial infarction combined with new-onset right bundle branch block - Li, Jingchao; Yu, Haijia; Cui, Luqian; Song, Huihui; Chu, Yingjie; Dong, Shujuan (Frontiers in Cardiovascular Medicine, 2023)
Background A few studies have focused on electrocardiography (ECG) parameters correlating with clinical prognosis in patients with acute myocardial infarction (AMI) combined with new-onset right bundle branch block (RBBB). Objective To assess the prognostic value of a new ECG parameter, namely, the ratio of QRS duration/RV6-V1 interval (QRS/RV6-V1), in patients with AMI combined with new-onset RBBB. Materials and methods A total of 272 AMI patients combined with new-onset RBBB who received primary percutaneous coronary intervention (P-PCI) were retrospectively enrolled in the study. First, the patients were divided into survival group and non-survival group. Demographic, angiographic, and ECG characteristics were compared between the two groups. Receiver operating characteristic (ROC) curve was used to screen the best ECG parameter for predicting 1-year mortality. Second, the ratio of QRS/RV6-V1, a continuous variable, was converted to the high ratio group and low ratio group according to the optimal cutoff value point determined by the X-tile software. We compared the patient’s demographic, angiographic, and ECG characteristics, in-hospital major adverse cardiovascular events (MACE), and 1-year mortality between the two groups. Multivariate logistic and Cox regressions were used to evaluate whether the ratio of QRS/RV6-V1 was an independent prognostic factor of in-hospital MACE and 1-year mortality. Results The ROC curve showed that the ratio of QRS/RV6-V1 had a higher value for predicting in-hospital MACE and 1-year mortality than the QRS duration, RV6-V1 interval, and RV1 interval. The patients in the high ratio group had significantly higher CK-MB peak and Killip class, lower ejection fraction (EF%), higher ratio of the left anterior (LAD) descending artery as infarct-related artery (IRA), and longer total ischemia time (TIT) than those in the low ratio group. The QRS duration was wider in the high ratio group than that in the low ratio group, whereas RV6-V1 was narrower in the high ratio group compared with that in the low ratio group. The in-hospital MACE rate (93.3% vs. 31.0%, p < 0.001) and 1-year mortality rate (86.7% vs. 13.2%, p < 0.001) in the high ratio group were higher than those in the low ratio group. The higher ratio of QRS/RV6-V1 was an independent predictor of in-hospital MACE (odds ratio, 8.55; 95% CI, 1.40–52.37; p = 0.02) after adjusting other confounders. Cox regression showed that the higher ratio of QRS/RV6-V1 predicted higher 1-year mortality of the patients with AMI combined with new-onset RBBB [hazard ratios (HR), 12.4; 95% CI, 7.26–21.22); p < 0.001] than the lower ratio of QRS/RV6-V1, and the HR still stayed at 2.21 even after a multivariable adjustment (HR, 2.21; 95% CI, 1.05–4.64); p = 0.037). Conclusion According to the results of our study, the high ratio of QRS/RV6-V1 (>3.0) was a valuable predictor of short- and long-term adverse clinical outcomes in AMI patients combined with new-onset RBBB. The implications of the high ratio of QRS/RV6-V1 were severe ischemia and pseudo synchronization between bi-ventricle.